Estimation of specific yield using water table fluctuations and cropped area in a hardrock aquifer system of Rajasthan, India - Chinnasamy, Pennan; Maheshwari, B.; Dillon, P.; Purohit, R.; Dashora, Y.; Soni, P.; Dashora, R. (Elsevier, 2018)
Assessment of specific yields is important for effective groundwater management in semi-arid hardrock aquifers, especially in India with its unsustainable groundwater usage rates. The Dharta watershed in the Udaipur district of Rajasthan is one such hardrock area in India where the groundwater extraction rate is a concern. In this study, we use groundwater balance analysis to estimate the specific yield (Sy) based on crop irrigation water use and changes in water table depths, during the irrigation season, to develop an understanding of the volume of groundwater recharge from pre and post monsoon water table depths and an understanding of the spatial and temporal changes in estimates of specific yield in the study area. The analysis used here estimates values at village scale (average area 3.65 km2) and is a technique compatible with the farmers monitoring of groundwater levels to facilitate local cooperative groundwater management. Five villages in the Dharta watershed in Rajasthan were selected and 50 wells per village were monitored for water table depth, at weekly intervals, over a two-year period. This resulted in a total of 250 wells in the study area and the monitoring was carried out by local farmer volunteers - called Bhujal Jankaars (BJs), a Hindi word meaning ‘groundwater informed.’ Crop area coverage (with a total of 40 crops) was examined for two years in the study area. Estimates of Sy in the five villages were between 1.4 and 8%, resulting in values comparable with previous studies. The watershed area-weighted average Sy was 3.8%. The method used in this study enabled estimates of recharge without needing a calibrated groundwater model in an area with sparse information on aquifer hydraulic characteristics and unreliable digital elevation maps.